Controlador nebuloso para motor de ignição por compressão operando com gás natural e óleo diesel - Ramos, Diego Berlezi (2006)
A foreseeable shortage of petroleum, associated to a growing ecological conscience, demand for alternative sources of energy and more efficient and less pollutant combustion processes. Among the few pollutant fuels this work approaches the combination of natural gas, whose consumption has been increasing year to year, and diesel. It is known that the internal combustion engines convert energy with low efficiency. Based on that, this work evaluates a bi-fuel Diesel engine, power by Diesel and natural gas as means of improving its efficiency. In the engine used as a prototype, the main energy comes from the combustion of natural gas. Being the gas the main fuel, the Diesel is used only to generate the pilot explosion for the combustion process. In this way, the diesel oil is partially substituted by natural gas, increasing the combustion efficiency. Initially it was made a study on the use of the natural gas in Diesel engine through a bibliographical revision. Therefore after, they were certain the parameters that should be monitored to develop an appropriate controller. It was verified that should be appraised the engine rotation and the injection angle. The performance aimed for the action of the loop control should be the rotation of the engine. The more appropriate control techniques were investigated for the management of the natural gas injection. When analyzing the traditional techniques it observed that they present some disadvantages as the mathematical complexity, difficulties in adapt the motor to the everchanging conditions of the motor with time/temperature, limitations in the grade of controller performance and complications for practical implementation on the part of non-specialized operators. To optimize the volume of natural gas supplied to the engine an electronic manager was developed for injection of this fuel. This electronic controller is based on an adaptive fuzzy algorithm to regulate the rate of injection of fuel, which was implemented through a microcontroller. The electronic injection system controls the timing of fuel injection, so managing the volume of gas supplied to each injection cycle. The injection angle is also accurately monitored by the control system. This topology, with few alterations, can be used in any Diesel engine operating in the bifuel mode. Results of this dissertation should contribute to increase the efficiency of Diesel engine as well as reduce the consumption of fuel and emission of pollutants.